2013
DOI: 10.1002/cncr.28341
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic characteristics of pancreatic neuroendocrine tumors and relation of somatostatin receptor type 2A to outcomes

Abstract: BACKGROUND:The impact of somatostatin receptor type 2 (SSTR-2a) expression levels on outcomes in patients with pancreatic neuroendocrine tumors (PNETs) has not been evaluated. METHODS: Correlations between clinicopathologic characteristics, including SSTR-2a expression and outcomes, were retrospectively studied in 79 patients with pancreatic neuroendocrine tumors (PNETs). RESULTS: The SSTR-2a score was 0 in 27% of patients, 1 in 24% of patients, 3 in 30% of patients, and 4 in 18% of patients. The overall survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
60
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 20 publications
6
60
3
Order By: Relevance
“…These findings are unlikely to be related to our SSTR staining score as they were confirmed in binary comparisons of ‘positive' versus ‘negative' tumours. This contrasts with previous reports regarding NETs [11,12,13,14], where SSTR expression was found to be associated with a better prognosis. This is probably related to the heterogeneous spectrum of NETs.…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations
“…These findings are unlikely to be related to our SSTR staining score as they were confirmed in binary comparisons of ‘positive' versus ‘negative' tumours. This contrasts with previous reports regarding NETs [11,12,13,14], where SSTR expression was found to be associated with a better prognosis. This is probably related to the heterogeneous spectrum of NETs.…”
Section: Discussioncontrasting
confidence: 55%
“…Both the level of SSTR expression and its prognostic value seem to be related to the degree of tumour differentiation in NETs. Most previous studies have assessed SSTR expression in well-differentiated NETs, which display high and intense expression of SSTR [11,12,13,14]. Corleto et al [13] demonstrated improved survival in patients with well-differentiated NETs who displayed expression of both SSTR2A and 5 in their tumours, together with a low Ki67 proliferative index, but neither SSTR2A nor SSTR5 alone were correlated with survival.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Overexpression of vascular endothelial growth factor receptors not only in the endothelial cells or in the stroma but also in the surface of the neuroendocrine cells has been extensively observed [23,24] . The presence of somatostatin receptors over the surface of pNETs tumor cells is over 90% [25,26] . Somatostatin receptors are playing a crucial role not only in the production and release of active peptides by the tumor cells but also in the growth and tumor cell survival process.…”
Section: Overcoming Resistances In Pnets: the Basic Science Perspectivementioning
confidence: 99%